2020
DOI: 10.21203/rs.3.rs-40507/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-dose Whole-lung Irradiation for COVID-19 Pneumonia: Short Course Results

Abstract: Abstract Objectives: The COVID-19 outbreak is affecting people worldwide. Most of the infected patients suffering from respiratory involvement that may progress to acute respiratory distress syndrome. This pilot study aimed to evaluate the clinical efficacy of low-dose whole-lung radiotherapy in patients with COVID-19 pneumonia. Methods: In this clinical trial, done in Iran, we enrolled patients with COVID-19 who were older… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 12 publications
4
26
1
Order By: Relevance
“…Other authors have thoroughly reviewed the rationale for radiotherapy in COVID-19 [108,109]. Preliminary reports have found that low-dose radiotherapy is safe for patients with COVID-19 and could be a useful therapeutic modality [110,111]. The combination of mild hyperthermia with low-dose radiotherapy could be a potentially beneficial therapy for patients with COVID-19.…”
Section: Thermotherapy Plus Radiotherapy In Covid-19mentioning
confidence: 99%
“…Other authors have thoroughly reviewed the rationale for radiotherapy in COVID-19 [108,109]. Preliminary reports have found that low-dose radiotherapy is safe for patients with COVID-19 and could be a useful therapeutic modality [110,111]. The combination of mild hyperthermia with low-dose radiotherapy could be a potentially beneficial therapy for patients with COVID-19.…”
Section: Thermotherapy Plus Radiotherapy In Covid-19mentioning
confidence: 99%
“…A second pilot study included 5 severe phase COVID-19 patients (median age 69), without matched controls. 50 These patients were hospitalized, demonstrated radiographic consolidations, and required supplemental oxygen. All 5 patients were treated with a single-dose LD-RT, 0.5 Gy, and were followed for 5-7 days to evaluate treatment response, clinical outcomes, and potential toxicity.…”
Section: Recent Clinical Trials Using Ld-rt For Severe Covid-19mentioning
confidence: 99%
“…25 Preliminary results from a clinical trial in Iran on 5 patients indicated this therapy may be as effective as it was in the 1940s against viral pneumonia. 26 It is important to note that 40 dying patients were invited to participate, but only 5 agreed. The other 35 chose to risk death rather than accept the perceived risk of a low dose of radiation.…”
mentioning
confidence: 99%